2018
DOI: 10.1136/tobaccocontrol-2018-054499
|View full text |Cite
|
Sign up to set email alerts
|

Youth access to JUUL online: eBay sales of JUUL prior to and following FDA action

Abstract: Online platforms may lack the will or expertise to effectively monitor content for tobacco products, while vendors quickly adapt to minor changes with simple strategies such as spelling variations. Accurate identification of online e-cigarette vendors is essential to the enforcement of policy and may benefit from cross-sector partnerships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Our study found that users of the UnderageJuul subreddit used different discreet approaches to circumvent relevant legal regulations to get JUUL. Some of these approaches (eg, purchase via eBay) are also reported in previous studies [9,16]. This study and the findings contribute to the literature by providing a detailed category dictionary for purchase approaches.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study found that users of the UnderageJuul subreddit used different discreet approaches to circumvent relevant legal regulations to get JUUL. Some of these approaches (eg, purchase via eBay) are also reported in previous studies [9,16]. This study and the findings contribute to the literature by providing a detailed category dictionary for purchase approaches.…”
Section: Discussionsupporting
confidence: 68%
“…[15]. Laestadius et al characterized the sale of JUUL products on eBay before a Food and Drug Administration (FDA) request to remove them, documented the impact of the request, and explored how eBay vendors bypassed FDA’s effort [16]. In addition, social media data have also been used to study JUUL-related communications and their impact.…”
Section: Introductionmentioning
confidence: 99%
“…Pods which give a nicotine surge were posted very frequently, and worryingly, there were many under-age followers recorded [78]. Despite efforts restrict youth access, these products can be obtained by young people of any age in stores or over the internet [79][80][81]. The Industry would have us debate whether or not vaping is a gateway to smoking.…”
Section: What Should Be Our Strategy To Protect Cyp?mentioning
confidence: 99%
“…1,[10][11][12][13][14][15][16][17][18][19][20][21] Although retailers cannot sell e-cigarettes to minors, these devices are frequently accessed via social means (eg, peers, family members) or directly purchased via online or in-person retailers. [22][23][24] The combination of high prevalence, public health ramifications, and social/environmental reinforcers of adolescent e-cigarette use has resulted in a call to action for e-cigarette prevention programs aimed at adolescents. 1,3,5 JUUL is the most used e-cigarette device among young persons, accounting for approximately 70% of the e-cigarette market at convenience stores in 2018.…”
mentioning
confidence: 99%